Predictors of purchasing intention of luxury goods among university students in Selangor - Osman, Syuhaily; Muhammad Arif, Afida Mastura; Cham, Xiau Yean (Malaysian Consumer and Family Economics Association, 2017)
Luxury goods can be anything that is desirable and more than a necessity and ordinary and these luxury goods tend to make life more pleasant for the buyer. Over the past few years, brand consciousness among the Malaysian society, especially the younger generation has been in the raising trend. The purpose of this paper was to examine the relationship between attitude, perceived brand, perceived quality, and perceived price with purchasing intention of luxury goods among university students in Selangor as well as to determine the most influential predictor of the purchasing intention. Multi-cluster sampling method was used to select a total of 300 respondents from Universiti Putra Malaysia and Multimedia University. The data were collected through a set of self-administrated questionnaire. The findings of Pearson correlation analysis demonstrated attitude (r=0.433, p=0.000), perceived brand (r=0.626, p=0.000), perceived quality (r=0.586, p=0.000) and perceived price (r=0.455, p=0.000) had significant positive relationship with purchasing intention. The multiple regression analysis showed that the most influential variable that predicts respondent’s purchasing intention was perceived quality (β = 0.428, p ≤ 0.001). This paper concluded that perceived brand, perceived quality and perceived price were significant predictors for purchasing intention of luxury goods, where perceived quality was the strongest predictor. The findings of the study have several implications that would be beneficial to the consumers in investigating the factors that will lead consumers to spend on luxury goods. Furthermore, the luxury goods producers can also plan on new business strategies that focus on quality of the goods since the result of the study showed that university students’ perception of quality of goods will trigger their purchasing intention of luxury goods the most. This paper can also serve as a guideline for future researchers and government to develop policies in order to expand the luxury markets in Malaysia.